Analisis Metode Weight Product untuk Penyiangan Buku - Ade Zulkarnain Hasibuan (LKP Unity Academy, 2024)
Book weeding is an important activity carried out to maintain the quality of library collections, ensuring that the books available are relevant and useful for users. Decision support system is a field of computer science that can help speed up the book weeding process, one of the methods that can be used is Weight Product. The Weight Product method was chosen because of its ability to handle multi-criteria and provide appropriate weights for each set of criteria. In this study, the criteria used for book weeding include book condition, year of publication, number of books, frequency of borrowing, and books that have the latest edition. Data is collected through surveys and statistical analysis of the existing book collection. Next, the Weight Product method is applied to calculate the final value of each book based on the predetermined criteria. The results of this calculation are used to identify books that deserve to be removed from the library collection. The results show that the application of the Weight Product method can improve the efficiency and effectiveness of the book weeding process. By using this method, libraries can make more objective and data-based decisions in determining which books need to be removed. In addition, this research also provides recommendations for other libraries who want to apply a similar method in their weeding process. Thus, this research not only contributes to the development of book weeding methods, but also provides new insights into the overall management of library collections.